Edukasi Gizi dan Pembinaan Kelompok Dasa Wisma dalam Pemanfaatan Pekarangan Berbasis Daun Kelor di Kecamatan Pauh Kamba, Padang Pariaman - Syahrial Syahrial; Helmizar Helmizar; Salma Nur Fitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Nutritional status is an essential indicator of children's health status because it is a risk factor for morbidity and mortality. Good nutritional status in children will contribute to their health in recovering from illness. Malnutrition is a condition in children's weight for age (BB/U) that does not match their age. Moringa leaf (Moringa oleifera) is a functional food from the monogeneric Moringaceae family and contains several minerals. The purpose of this community service was to empower the Dasa Wisma group to utilise the community's yard by planting Moringa to improve the nutritional status of toddlers and reduce Stunting rates. This service was carried out from April to July 2022 at the Stunting locus, i.e. Pauh Kamba District, Padang Pariaman Regency. The activities included coaching the Dasa Wisma group regarding Stunting, how to overcome Stunting, processing Moringa leaves as a source of nutrition and family income, and evaluating Dasa Wisma group activities in processing Moringa leaves into food. The partnership program is expected to have sustained assistance from an expert to the community in the village.